Investigation of dielectric virial coefficients of methoxyacetic acid - Murthy, MBR; Patil, RL; Dayasagar, BS (2003)
Dielectric virial coefficients throw light on short-range molecular interactions. This provides an insight into solute dimerization. An attempt is made to evaluate dielectric virial coefficients of methoxy acetic acid in three solvents. Using the first virial coefficient the apparent solution moment of methoxy acetic acid is calculated.